2017
DOI: 10.1002/pssa.201700042
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature fabrication of Ag(In,Ga)Se2 thin films for applications in solar cells

Abstract: Molecular beam epitaxy was used to fabricate Ag(In,Ga)Se 2 (AIGS) thin films. To improve the diffusion of Ag, hightemperature deposition and high-temperature annealing methods were applied to fabricate AIGS films. The as-grown AIGS thin films were then used to make AIGS solar cells. We found that grain size and crystallinity of AIGS films were considerably improved by increasing the deposition and annealing temperature. For high-temperature deposition, temperatures over 600 8C led to decomposition of the AIGS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…[30] The selected selenization temperature for ACIGSe (510 °C) is substantially lower than that of CIGSe (590 °C) because the phase decomposition (Ag 2 Se) occurs at a high selenization temperature for ACIGSe. [31] Although the selenization temperature is reduced for ACIGSe, Ag-alloying can still induce grain growth at a low selenization temperature possibly due to the presence of a liquid AgInSe 2 phase for T-ACIGSe during selenization. [13] The cross sectional view of the scanning electron microscopy (SEM) images clearly identifies the enhanced grain growth for T-ACIGSe (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[30] The selected selenization temperature for ACIGSe (510 °C) is substantially lower than that of CIGSe (590 °C) because the phase decomposition (Ag 2 Se) occurs at a high selenization temperature for ACIGSe. [31] Although the selenization temperature is reduced for ACIGSe, Ag-alloying can still induce grain growth at a low selenization temperature possibly due to the presence of a liquid AgInSe 2 phase for T-ACIGSe during selenization. [13] The cross sectional view of the scanning electron microscopy (SEM) images clearly identifies the enhanced grain growth for T-ACIGSe (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the corresponding devices obtained had 9.4% PCE. Simultaneously, Nakada et al 67 used high deposition and annealing temperatures to prepare AIGS thin films. It is shown that at higher deposition and annealing temperatures, the diffusion rate of Ag is higher, and its distribution is more uniform.…”
Section: New Atfscs: Materials and Devicesmentioning
confidence: 99%
“…Most studies investigating the role of Ag insertion in the absorber layer have focused on standard GGI profiles without a detailed explanation of the effects of high Ga concentrations in (Ga,Cu)­(In,Ga)­Se 2 (ACIGS) solar cells. For example, the substitution of Ag or Cu and the resulting slight bandgap widening can be attributed to anion displacement/bond length effects, changes in the s–s orbital repulsion in the conduction band minimum, or changes in the p–d orbital repulsion in the valence band maximum. , The presence of liquid channels comprising Ag–Se along the grain boundaries (GBs) enhances Ga interdiffusion, improves the grain size, and facilitates the recrystallization of CIGS at relatively low temperatures. Additionally, the incorporation of Ag mitigates the degree of structural disorder within the CIGS lattice by lowering the melting point of (Ag,Cu)­(In,Ga)­Se 2 (ACIGS) chalcopyrites. , Similar improvements have been observed for Ag-alloy CIGS. In this context, the current study leveraged the tunable bandgap property of CIGS to precisely tailor the shape of the double Ga grading profile in both the notch and back regions of CIGS and ACIGS solar cells. This study’s findings reveal the beneficial impact of a sizable columnar grain structure with high Ga content near the back surface contact, facilitating Ga diffusion and reinforcing defect annihilation.…”
Section: Introductionmentioning
confidence: 99%